Critical Factors of Effectiveness of Environmental Management Plan (EMP) of Oil and Gas Projects in the Niger Delta Region of Nigeria - Hemba, Stephen; Usman, Abdullahi Bala (International Journal of Research in Interdisciplinary Studies, 2025)
Oil and gas production activities have been going on in the Niger Delta region of Nigeria since 1958. The mandatory use of EMP to mitigate the impacts on the environment has not been effective. Researchers have not investigated to a deeper extent the key elements that will enhance the effectiveness of EMP’s of the oil and gas projects. This makes it difficult to tailor impactful policies and resources to turn things around and achieve environmental sustainability in the context of oil and gas production activities in the Niger Delta region. This study determined critical factors of effectiveness of EMP in oil and gas projects in the region. The Study involved administration of a semi structured questionnaire on 384 respondents comprising the proponent, regulator and community. The data was analysed using Principal Component Analysis (PCA). The PCA identified a) Collective address of impacts by all stakeholders; b) Commitment; c) Importance of impact data; d) Monitoring and Evaluation and e) Information sharing as critical factors of effectiveness of EMP in the region.